Humins as promising material for producing sustainable carbohydrate-derived building materials. (15th May 2017) - Mija, Alice; van der Waal, Jan C.; Pin, Jean-Mathieu; Guigo, Nathanael; de Jong, Ed
Graphical abstract: Highlights: Humins are original unique macromolecules, sub-products during polysaccharide conversion. Furfuryl alcohol/humins resins with good viscosity, stability and curing behaviour were prepared. New thermosetting materials suitable for applications in a.o. building products were produced. Abstract: Nowadays biobased building materials are used in various fields and for a wide range of applications such as polymers, fillers, coatings, adhesives, impregnation materials or high performance composites. This work focuses on humins, a biomacromolecular by-product of a HydroxyMethylFurfural/FuranDiCarboxylic Acid biorefinery. Humins are obtained by acidic treatment of polysaccharides and show very interesting potential as a reactive, semi-ductile thermoset matrix to impregnate cellulosic fibres. Therefore, humins have the essential characteristics to develop a new class of thermoset materials and composites, offering excellent possibilities to increase the renewable carbon content of the final products and improve its properties. A proper characterization of the neat humins in terms of solubility, flow behaviour and thermal resistance is essential in order to find the optimal parameters of processing humins solutions as well as co-reactive mixtures for impregnations or to prepare composites. In addition the study further indicates that humins enhance the modulus and the tensile strength of pure polyfurfurylalcohol resins. It was also shown that there is a difference in behaviour when sulfuric acid or maleic anhydride is used as initiator. The most optimal initiator will depend on application and preferred processing conditions. These encouraging results assure an important future for humins as economic green matrix for the production of composites and wood impregnation.